Privatisation of S&T Information Services : The INSDOC Experience - Dhaka, R.P.S.; Arora, Kamlesh (DESIDOC Journal of Library & Information Technology, 2002)
The paper discusses the INSDOC's experience in privatisation of information products and services, It discusses the elements of privatisation in routine jobs of data entry, data validation, editing etc. for database creation and library automation projects, by contracting/sub-contracting such jobs to private parties and using the staff for taking up new projects. It concludes that privatisation of information services is economically viable and has proved successful in INSDOC. http://dx.doi.org/10.14429/dbit.15.5.3200